Analysis of the Influence of Machine Operation Parameters on the Technical Characteristics of the Elevator in the Point of Cleaning and Washing of the Equipment Park - Bohomaz, V. M.; Nagachevskyi, V. J.; Pryimak, M. V. (Science and Transport Progress, 2024)
Purpose. The study is aimed at determining the nature of the influence of the operating parameters of the enterprise’s machines (the number of tracked and wheeled machines, the annual consumption rates of their motor resources) on the technical characteristics of the elevator for cleaning the dirt settler of the vehicle cleaning and washing equipment park, in particular, the height of the elevator and its productivity, as well as building analytical and graphical dependencies of these values on the operating parameters of the machinery. Methodology. To achieve this goal, we used the calculation algorithms presented in the modern technical literature and analyzed the factors and values that affect the height and capacity of the elevator of the station. It has been established that in order to determine the design parameters of the elevator, it is necessary to have statistical data on the operation of machinery at the enterprise and to carry out a detailed calculation, which includes: the mathematical expectation of the average daily number of machine trips from the fleet for different types of machinery, as well as the total value, the number of numbered machine servicing, the number of external machine washing stations, and the geometric parameters of the dirt tank. Findings. A graphical analysis of the influence of the number of tracked and wheeled vehicles and their annual consumption rates of motor resources on the value of its height and productivity was carried out for the elevator of the cleaning and washing station of the fleet of a particular enterprise, which is intended for cleaning the sludge tank. It was found that the functions of change in productivity and height are linearly increasing (with other parameters fixed). Originality. The authors first investigated the dependencies of the design parameters (height and capacity) of the elevator, built analytical dependencies of the mathematical expectation of the average daily number of machine trips for wheeled and tracked vehicles on the number of relevant machines and annual motor resource consumption rates, as well as the height and capacity of the elevator. For the examples of enterprise fleets with equipment operation parameters taken from statistical data, a graphical analysis of the constructed dependencies was carried out. Practical value. The use of the constructed dependencies makes it possible to determine the general nature and range of changes in the above design parameters in the case of varying equipment performance at a particular enterprise. The proposed dependencies can be used to quickly determine the required design parameters of an elevator based on specific data on the operation of equipment.